Judging Values and Participation in Mental Capacity Law - Camillia Kong; John Coggon; Michael Dunn; Penny Cooper (Laws, 2019)
Judges face a challenging task in determining the weight that ought to be accorded to the person (P)’s values and testimony in judicial deliberation about her capacity and best interests under the Mental Capacity Act 2005 (MCA). With little consensus emerging in judicial practice, incommensurable values drawn from divergent sources often collide in such cases. This paper outlines strict and flexible interpretations of the MCA’s values-based approach to making decisions about capacity and best interests, highlighting the problematic implications for the normative status of P’s values and the participatory role of P in judicial deliberations. The strict interpretation draws a false separation between ascertaining P’s values and the intrinsic value of enabling P’s participation in court proceedings; meanwhile, the flexible interpretation permits judicial discretion to draw on values which may legitimately override the expressed values of P. Whether in the ambiguous form of internal and/or extra-legal judicial values, these value sources demand further scrutiny, particularly regarding their intersection with the values held by P. We offer provisional normative guidelines, which set constraints on the appeal to extra-legal values in judicial deliberation and outline further research pathways to improve the justification around judicial decisions regarding P’s participation.